Human salivary α-amylase (EC.3.2.1.1) activity and periodic acid and schiff reactive (PAS) staining: a useful tool to study polysaccharides at an undergraduate level - Fernandes, Ruben (2021)
Health science education is presently in discussion throughout Europe due to the Bologna Declaration. Teaching basic sciences such as biochemistry in a health sciences context, namely in allied heath education, can be a challenging task since the students of preclinical health sciences are not often convinced that basic sciences are clinically valuable (J. R. Rudland, S. C. Rennie ( 2003) The determination of the relevance of basic sciences learning objectives to clinical practice using a questionnaire survey, Med. Educ. (Oxf.) 37, 962-965; E. C. Wragg ( 2003) How can we determine the relevance of basic sciences learning objectives to clinical practice?, Med. Educ. ( Oxf.) 37, 948-949). Thus, nowadays teachers are compelled to use their imagination to be able to elaborate laboratory sessions aiming for the understanding of theoretical concepts that are also clinically related: in other words, basic concepts and skills that underlie the competencies demanded of the future health professional. In the present work, we describe a set of laboratory sessions implemented in the discipline of biochemistry, belonging to the first year of several courses of allied health professionals, which can also be implemented in other health sciences courses. These sessions focus on the characteristics and properties of carbohydrates. The exercises we propose include two different laboratory practical sessions based on a histopathological routine technique known as periodic acid and Schiff reactive that is currently used to detect sugar metabolic and tumor diseases ( J. M. T. Rivera, C. T. Lopez, B. C. Segui ( 2001) Bioquimica Estructural: Conceptos y Tests, Tebar Flores, Madrid). The methodology described enables the demonstration of some biochemical properties of polysaccharides, namely animal and vegetable, and the catalytic activity of the human salivary alpha-amylase (EC.3.2.1.1) enzyme. A further comparison between alpha-amylase activity in vitro and in situ is also possible by the proposed methodology. Additionally, to this extent, a comparison between the results of the learning improvement that occurred after the implementation of this tool is presented.